V2G based bidirectional EV charger topologies and its control techniques: a review - Rana, Rahul; Saggu, Tejinder Singh; Letha, Shimi Sudha; Bakhsh, Farhad Ilahi (Discover applied sciences, 2024)
In recent years, the integration of bidirectional converters in the grid for V2G (vehicle-to–grid) applications of Electric Vehicles (EVs) has gained significant attention due to its potential to enhance grid stability, energy efficiency, and economic benefits. This analytical review highlights the different topologies of bidirectional converters and discusses various control techniques for efficient power flow between the vehicle and grid to enhance the performance of V2G and G2V functionalities. Further, the topologies of bidirectional converters highlighting key parameters such as the count of switches and their voltage stress, current ripple, efficiency, etc., are explored. The distinct advantages and limitations of each classification are also discussed. Many multilevel topologies that generate significant gain with low stress on switches and lesser harmonics have also been reviewed. The review then examines various control strategies, including power flow control and voltage regulation. These techniques are classified according to their control methodologies, which include traditional proportional-integral (PI) control, predictive control, sophisticated model-based control, and optimization. The synthesis of current advances in bidirectional converters and control techniques sheds light on developing trends and technologies, identifying important problems and future research objectives in the field. The economic and environmental implications of the G2V and V2G case studies also reinforce the review. Thus, this evaluation aims to promote further breakthroughs in EV integration with the grid, eventually leading to a more sustainable and resilient energy ecology. Article highlights The key points of the paper are: Different converter topologies for G2V & V2G and their impact on the grid are discussed and compared. A critical analysis of state of art control methodologies applied to DC/DC converters has been discussed. Advanced optimization algorithms for smart and coordinated charging of an EV are presented.